2009
DOI: 10.1093/geront/gnp079
|View full text |Cite
|
Sign up to set email alerts
|

Walking and the Preservation of Cognitive Function in Older Populations

Abstract: This investigation provides insight into the extent to which walking is associated with preservation of cognitive health, setting the stage for future longitudinal studies and community-based interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 20 publications
2
42
1
Order By: Relevance
“…In contrast, we hypothesized that walking-based mobility may be only weakly influenced by the three cognitive abilities because walking predominantly takes place in familiar everyday environments, particularly in the residential neighborhood of older adults (Eyler et al 2003;Prohaska et al 2009), and is mostly executed in an automatic and routine-like manner.…”
Section: Hypothesesmentioning
confidence: 99%
“…In contrast, we hypothesized that walking-based mobility may be only weakly influenced by the three cognitive abilities because walking predominantly takes place in familiar everyday environments, particularly in the residential neighborhood of older adults (Eyler et al 2003;Prohaska et al 2009), and is mostly executed in an automatic and routine-like manner.…”
Section: Hypothesesmentioning
confidence: 99%
“…While reliant on the functioning of peripheral organs such as the musculoskeletal system, vestibular apparatus, and cardiovascular fitness, normal gait performance also depends on cortical input. Walking is the most common form of physical activity among older adults [28], is increasingly being examined as a means of health promotion and disease prevention, and has been suggested as being protective for cognitive health [9]. Although there is evidence that walking may be protective of cognitive status, there are findings that suggest that walking speed can also be used as a determinant of cognitive function [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence that walking may be protective of cognitive status, there are findings that suggest that walking speed can also be used as a determinant of cognitive function [29]. It has been demonstrated in community-based studies in older adults that cognitive decline and dementia are strongly associated with higher risk of developing subsequent slow gait speed, especially in advanced states [30][31], and lower frequency of walking in the neighborhood [9]; also, decreases in cognition and gait speed have been found to be parallel over time [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duff et al 31) also found that global cognition was related to walking speed. Furthermore, Prohaska et al 32) reported that the community setting where people walk and the intensity of walking within their neighborhood were significantly associated with cognitive status. Older adults with lower Mental Alternation Test (MAT) scores were more likely to walk in indoor shopping malls rather than in parks, whereas, those with higher cognitive function scores on the MMSE were less likely to walk in indoor gyms.…”
Section: Relationship Between Cognitive Function and Physical Fitnessmentioning
confidence: 99%